ANALYSIS OF THE RELIABILITY OF THE BUILDING SAFETY SYSTEM IN KI HADJAR DEWANTARA KODIKLATAL BUILDING ON FIRE HAZARDS PREVENTION - Dodiek Alfianzi; Avando Bastari; Okol Sri Suharyo (Indonesian Naval Technology College STTAL, 2020)
ABSTRACT This study aims to determine the reliability value of the fire system and the safety of the KI Hadjar Dewantara building in the case of a fire. This research questionnaire was conducted twice. The Analytical Hierarchy Process (AHP) method will be applied to the first questionnaire to obtain the weighting of the fire variables which includes site completeness, rescue facilities, passive protection systems, and active protection systems. The second questionnaire used the check-list method based on the Minister of Public Works Regulation Number 26 of 2008 to determine the reliability value of the building in the event of a fire. The results for the reliability value of the Ki Hadjar Dewantara building from Mako Kodiklatal using the AHP method and the check-list respectively are as follows: 91.93% and 91.45%. So, it can be concluded that the building security system in case of a fire is in “Good” condition. Keywords: Fire, Reliability, AHP